Diskresi Kebijakan Alokasi Dana Desa Era Pandemi di Desa Belatung Ogan Komering Ulu - Plando, Plando; Djakfar, Yunizir; Saleh, Rakhmat (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2023)
The Sake of guaranteeing maximum public service delivery and guaranteeing people's welfare, the government has a certain freedom to take action based on its own judgment in overcoming various conditions that require prompt and appropriate handling. This study aims to see how to know the discretion that exists in the village fund allocation policy in the era of the covid pandemic in Belatung Village, Lubuk Batang District, Ogan Komering Ulu Regency. This research uses a qualitative description research method which is carried out by explaining the problem to the research object which is explored in depth. It is considered that the implementation of employee discretionary practices at the Street Level Bureaucracy still lacks initiative. village officials in responding to service difficulties they faced chose to take action by asking the leadership for directions or delaying services until the leadership arrived, the apparatus provided more services to the public based on standard or formal rules and only a small number of apparatus adapted the situation to the existing services.